Prozone effects in microscopic agglutination tests for leptospirosis in the sera of mice infected with the pathogenic Leptospira interrogans serovar Canicola - Shimabukuro, Fabio Hiroto; Costa, Veruska Maia Da; Silva, Rodrigo Costa da; Langoni, Hélio [UNESP]; Silva, Aristeu Vieira da; Carvalho, Lidia Raquel de; Domingues, Paulo Francisco [UNESP] (Instituto Oswaldo Cruz, Ministério da Saúde, 2013)
Mice experimentally infected with a pathogenic strain of Leptospira interrogans serovar Canicola produced false negative results (prozone effect) in a microscopic agglutination test (MAT). This prozone effect occurred in several serum samples collected at different post-infection times, but it was more prominent in samples collected from seven-42 days post-infection and for 1:50 and 1:100 sample dilutions. This phenomenon was correlated with increased antibody titres in the early post-infection phase. While prozone effects are often observed in serological agglutination assays for the diagnosis of animal brucellosis and human syphilis, they are not widely reported in leptospirosis MATs.
Keywords: microscopic agglutination test; prozone effect; leptospirosis